Recognizing biography - Epstein, William H. (Anniversary Collection., 1987)
Epstein's narrative interweaves interpretive and theoretical chapters as it emplots the discourse of English biography from Walton to Strachey. In this way familiar generic relationships between biographer, subject, life, text, falsehood, and readership are analyzed in specific (if constantly shifting) historical, literary, cultural, and economic texts.